A novel antifouling and antibacterial surface‐functionalized PVDF ultrafiltration membrane via binding Ag/SiO2 nanocomposites. Issue 3 (29th June 2016) - Pan, Yang; Yu, Zongxue; Shi, Heng; Chen, Qi; Zeng, Guangyong; Di, Haihui; Ren, Xiaoqing; He, Yi
Abstract: BACKGROUND: Membrane fouling is a main obstacle hindering wider application of membrane technologies, and can cause a decline in flux and increased energy consumption, and more frequent chemical or membrane replacement can increase the operating costs. Membrane fouling is mainly governed by organic fouling and biofouling. In recent years, the development of new materials has provided new methods and thoughts for the research and development of antifouling and antibacterial membranes. RESULTS: In this study, to obtain both a highly hydrophilic, antifouling and antibacterial poly(vinylidene fluoride) (PVDF) membrane, in situ formed silver (Ag) nanoparticles were immobilized with silica (SiO2 ) nanoparticles, and then chemically bound onto a PVDF ultrafiltration (UF) membrane surface. The surface modification processes were achieved through a remarkably facile and effective dip‐coating method. The impacts of Ag/SiO2 nanocomposites on membrane performance were investigated when applied in membrane filtration processes simultaneously. This membrane showed higher hydrophilicity and water permeation flux. The PVDF membrane exhibited antibacterial properties and displayed better anti‐fouling performance. CONCLUSION: The superior performance of the Ag/SiO2 ‐PVDF membranes and this facile, effective and scalable modification method hold great promise for their practical application. This work would also be helpful for developing new antifouling and antibacterial membrane and related materials via a convenient and large‐scale method. © 2016 Society of Chemical Industry